Advances in Thrombolytic Therapies for Venous Thromboembolism: A Review of Contemporary Approaches and Technologies - Tomaszek, Kamil; Paul, Jonathan; Ahmed, Osman (Seminars in Interventional Radiology, 2025)
New catheter-based technologies in the treatment of thrombolysis of venous thromboembolism have changed the landscape of the treatment of that disease spectrum. Traditional catheter-directed thrombolysis (CDT) typically involved placement of a lysis catheter and infusion of thrombolytic medications in the ICU setting for many hours, requiring frequent monitoring of fibrinogen, and titration of the thrombolytic agent based on patient-reported symptom improvement and standard vital signs. However, new devices and studies have shown effectiveness with significantly shorter infusion times and medication use, and have introduced features that may help to personalize therapy and help to preserve resources such as ICU bed allocation. This review examines the most recent advances in thrombolysis technology focusing on innovative devices and their clinical implications.
Keywords: interventional radiology; pulmonary embolism; venous thrombosis; lysis; technology; catheter-directed therapy